FAO fisheries report N.547 supp - FAO (FAO, 1997)
The first section consists of papers which discuss the issues of wastage reduction, selectivity of fishing practices, utilization of presently discarded catch and management measures that are being or have been made in various countries to reduce wastage and discards. The second section contains papers which review the bycatch and discards problem in various regions and endeavour to quantify and qualify the magnitude of wastage. Comparisons are made with earlier estimates given in FAO Fisheries Technical Paper No.339 - A Global Assessment of Fisheries Bycatch and Discards